Pengaruh Kompensasi, Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan Divisi Penjualan di PT Mandiri Sumber Kemakmuran Cabang Simpang Cilegon (International Forum of Researchers and Lecturers, 2025)
The research aims to determine whether there is an influence of compensation, work environment and work stress on employee performance at PT Mandiri Sumber Kemakmuran Simpang Cilegon Branch. The total population is 40 sales and marketing people at PT Mandiri Sumber Kemakmuran, all of whom were respondents in this research. Data was obtained using a questionnaire distributed to all sales and marketing at PT Mandiri Sumber Kemakmuran Simpang Cilegon Branch. The data analysis technique used in this research is multiple linear regression, which is operated using the SPSS Version 25 program. The result of this research show that there is a significant and positive influence of the compensation variables (X1), work environment (X2) and work stress (X3) on employee performance (Y).